Directionally solidified high-entropy (Y0.2Gd0.2Ho0.2Er0.2Yb0.2)3Al5O12/Al2O3 eutectic with outstanding crystallographic texture formation capability. (November 2022) - Zhou, Cui; Luo, Zhaoping; Du, Tiefeng; Sun, Haofei; Wang, Jiemin; Sun, Luchao; Wang, Jingyang
Abstract: Crystallographic texture control is the critical challenge for directionally solidified eutectic (DSE) ceramics. We herein report a high-entropy (Y0.2 Gd0.2 Ho0.2 Er0.2 Yb0.2 )3 Al5 O12 /Al2 O3 DSE ceramic that shows outstanding crystallographic texture formation capability. Based on comprehensive observations of phase composition and eutectic microstructure characteristics, the single crystal phases of high-entropy (5RE0.2 )3 Al5 O12 (RE = rare earth) and Al2 O3 are obtained within a much-shortened growth distance (within 15 mm) than those of the single rare earth containing RE3 Al5 O12 /Al2 O3 counterparts (typically ≥ 80 mm). The rapid formation of stable crystallographic texture is significant for microstructure control in DSE processing and uniformity of mechanical property along the whole material. Graphical abstract: Image, graphical abstract